The Impact of Irrigation Schemes on Farmers Income and Livelihoods in Region of India: Enhancing Agricultural Prosperity and Sustainability through Irrigation Schemes in India (Journal of Advances and Scholarly Researches in Allied Education, 2020)
Agricultural Policy 2020, is centred around farmers' prosperity and is figured to expand on the characteristic qualities of its agribusiness and associated areas, to address the limitations it faces and to utilize assets and openings arising because of advancement in technology, and the emergence of quickened monetary development in the state and the country. The current policy expects to give additionally push to the achievement conveyed through deliberate efforts under the past agricultural arrangements of the state. The point is to complete the huge undiscovered capability of horticulture and fortify the monetary and social prosperity of its farmers, tenant farmers and landless agricultural family units while guaranteeing the development cycle is ecologically, monetarily and mechanically comprehensive, adaptable and supportable.